Below-the-ankle Angioplasty: Current Evidence and Future Perspectives - Stavros Spiliopoulos (Radcliffe Medical Media, 2019)
Over 20 million adults in Europe suffer from peripheral arterial disease (PAD). The annual incidence of PAD is approximately 2.4%, while the annual incidence of critical limb ischaemia (CLI), the last and most severe stage of PAD, has been reported to be 0.4%. Endovascular angioplasty and/or stenting of infrapopliteal disease is, today, an established treatment for critical limb ischaemia. The main technical advantages of endovascular treatment over open bypass surgery include the possibility to revascularise more than one infrapopliteal vessels and, most importantly, to treat outflow pedal vessel disease or even reconstitute the pedal arch. Data of below-the-ankle angioplasty are beginning to sum up and the contribution of pedal arch angioplasty in limb salvage and wound healing are currently under investigation. In this review, currently available data and the future perspectives on below-the-ankle and pedal arch endovascular treatment will be presented.